Learning Lessons from Disasters: Alternatives to Royal Commissions and Other Quasi‐Judicial Inquiries1. Issue 4 (20th January 2015) - Eburn, Michael; Dovers, Stephen
Abstract : With over 50 inquiries in 75 years, Australian communities continue to suffer from the impact of extreme events whether fires, floods, cyclones, or other emergencies. Einstein is reported to have said 'Insanity: doing the same thing over and over again and expecting different results'. The insanity may not lie in responding to fires and emergencies the same way, and facing another tragedy, but in reviewing these events in the same way and expecting the quasi‐judicial process to identify how to prevent the next one. This paper argues that it is time to do the post‐event review in a different way and suggests some possible options for new approaches to learning lessons from tragedy. Abstract : With over 50 inquiries in 75 years, Australian communities continue to suffer from the impact of extreme events. This paper argues that it is time to do the post‐event review in a different way and suggests some possible options for new approaches to learning lessons from tragedy.